Vacuolar protein sorting-associated protein Vps17 regulates sexual reproduction and virulence of Cryptococcus neoformans - Meng-Ru Guo; Jie-Shu Guo; Jun-Ming Chen; Tong-Bao Liu (Mycology)
Cryptococcus neoformans, an opportunistic fungal pathogen, poses significant health risks by causing severe meningitis in both immunocompromised and immunocompetent individuals. In this study, we identified the vacuolar protein sorting-associated protein Vps17, a crucial Retromer complex component, in C. neoformans. Sequence analysis revealed that Cryptococcus Vps17 contains a PX and a BAR domain, classifying it within a conserved family of SNX proteins interacting with inositol phosphate. Expression pattern analysis indicated that the VPS17 gene is active throughout all developmental stages of C. neoformans, with Vps17 localised on vesicles and unaffected by external stressors. Deletion of the VPS17 gene resulted in reduced fungal capsule size and increased sensitivity to various stressors like SDS, NaCl, and KCl, highlighting its role in maintaining cell membrane integrity. Significantly, the absence of Vps17 hindered sexual reproduction, preventing basidiospore formation and meiosis following nuclear fusion. In a murine systemic infection model, the virulence of the vps17Δ mutant was significantly reduced. Our findings suggest that Vps17 plays a vital role in regulating sexual reproduction and pathogenicity in C. neoformans by influencing the expression of numerous related genes.